2024
DOI: 10.1021/acsanm.4c00512
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Growth of Dual-Semiconductor Coshells on Au Nanorods with Tunable Band Arrangements for Efficient Photocatalysis

Zi-Xing Zheng,
Xi Liang,
Hao Lin
et al.

Abstract: Metal core@semiconductor shell hybrids are regarded as promising candidates for plasmon-enhanced photocatalysis, but it remains a challenge to build semiconductor junctions on the shell region for further improved photocatalysis. Herein, Au core@dualsemiconductor coshell hybrids, whose shell was made by two different metal sulfides, were prepared by a one-pot direct growth method based on Au nanorods for highly improved photocatalysis for the first time. By inducing two different metal ions at the step of shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Various studies can be found in the literature on the kinetics of photocatalytic and photo-Fenton degradation of pollutants. Generally, photo-Fenton degradation follows pseudo-first-order kinetics, wherein the production of major reaction radicals gets accelerated due to the redox reaction of Fe or Fe-like species. Instead, the kinetics of photocatalysis can encompass a range of behaviors, including pseudo zero-order, pseudo-first-order, or pseudo-second-order reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies can be found in the literature on the kinetics of photocatalytic and photo-Fenton degradation of pollutants. Generally, photo-Fenton degradation follows pseudo-first-order kinetics, wherein the production of major reaction radicals gets accelerated due to the redox reaction of Fe or Fe-like species. Instead, the kinetics of photocatalysis can encompass a range of behaviors, including pseudo zero-order, pseudo-first-order, or pseudo-second-order reactions .…”
Section: Introductionmentioning
confidence: 99%